2004
DOI: 10.1099/mic.0.26635-0
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas syringae pv. phaseolicola can be separated into two genetic lineages distinguished by the possession of the phaseolotoxin biosynthetic cluster

Abstract: The bean (Phaseolus spp.) plant pathogen Pseudomonas syringae pv. phaseolicola is characterized by the ability to produce phaseolotoxin (Tox + ). We recently reported that the majority of the Spanish P. syringae pv. phaseolicola population is unable to synthesize this toxin (Tox " ). These Tox " isolates appear to lack the entire DNA region for the biosynthesis of phaseolotoxin (argK-tox gene cluster), as shown by PCR amplification and DNA hybridization using DNA sequences specific for separated genes of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Nevertheless, it has been reported that the majority of the Spanish isolates of P. syringae pv. phaseolicola are unable to synthesize phaseolotoxin due to the absence of the entire argK-tox cluster (González et al, 2003;Oguiza et al, 2004;Rico et al, 2003). Genomic differences, including pathogenicity gene content and location, prompted the separation of toxigenic and non-toxigenic isolates into two distinct lineages, termed Pph1 and Pph2, respectively (Oguiza et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been reported that the majority of the Spanish isolates of P. syringae pv. phaseolicola are unable to synthesize phaseolotoxin due to the absence of the entire argK-tox cluster (González et al, 2003;Oguiza et al, 2004;Rico et al, 2003). Genomic differences, including pathogenicity gene content and location, prompted the separation of toxigenic and non-toxigenic isolates into two distinct lineages, termed Pph1 and Pph2, respectively (Oguiza et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…phaseolicola are unable to synthesize phaseolotoxin due to the absence of the entire argK-tox cluster (González et al, 2003;Oguiza et al, 2004;Rico et al, 2003). Genomic differences, including pathogenicity gene content and location, prompted the separation of toxigenic and non-toxigenic isolates into two distinct lineages, termed Pph1 and Pph2, respectively (Oguiza et al, 2004). These studies were performed with isolates from Castilla y Leó n (94 223 km 2 ), the largest dry bean producing region of Spain, where most of the crop is dedicated to common bean landraces of different varieties (riñó n, canela, pinta, morada, palmeña, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, all the P. syringae pv. phaseolicola tox-strains analyzed so far also lacked other genes of the phaseolotoxin biosynthesis cluster and failed to produce phaseolotoxin (Rico et al, 2003;Oguiza et al, 2004). Additionally, the tox-isolates also failed to react with one of the few commercial antibodies for the serological detection of P. syringae pv.…”
mentioning
confidence: 99%
“…However, it was recently showed that more than 66% of the P. syringae pv. phaseolicola isolates causing field epidemics in Castilla y León, Spain, were nontoxigenic and did not contain DNA specific for the biosynthesis of phaseolotoxin (Rico et al, 2003;Oguiza et al, 2004). The strains of P. syringae pv.…”
mentioning
confidence: 99%
See 1 more Smart Citation